Origin of the isotopic composition of natural perchlorate: Experimental results for the impact of reaction pathway and initial ClOx reactant. (15th October 2021) - Estrada, Nubia L.; Anderson, Todd A.; Böhlke, J.K.; Gu, Baohua; Hatzinger, Paul B.; Mroczkowski, Stanley J.; Rao, Balaji; Sturchio, Neil C.; Andrew Jackson, W.
Abstract: Natural perchlorate (ClO4 − ) exists in many places on Earth, in lunar regolith, meteorites, and on the surface of Mars. Terrestrial natural ClO4 − has widely variable Cl and O stable isotopic compositions (δ 37 Cl, δ 18 O, Δ 17 O). The δ 18 O and Δ 17 O values of ClO4 − from the most hyper-arid locations co-vary. ClO4 − from less arid areas has relatively little 17 O excess and poor Δ 17 O-δ 18 O correlation. ClO4 − from the Atacama Desert has unusually low δ 37 Cl (<−10‰) and exhibits a positive correlation between δ 37 Cl and δ 18 O, while the δ 37 Cl of ClO4 − from all other locations varies between −5 and +7‰ with no δ 37 Cl-δ 18 O covariation. To evaluate the impact of different precursors (ClOx ) and reaction pathways on the isotopic composition of ClO4 −, we measured the isotopic composition of ClO4 − produced in the laboratory by UV or O3 mediated aqueous oxidation of Cl −, OCl −, ClO2 −, and ClO2 ° as well as O3 mediated oxidation of dry NaCl. ClOx oxidation in aqueous or dry systems enriched in O3 produced ClO4 − with Δ 17 O values that generally increased with the number of O atoms required and included evidence that the site-specific 17 O anomaly in O3 was preferentially transferred to ClO4 − . Based on the inferred number of O atoms sourced from O3, and known Cl and O reaction pathways, it appears that ClO2 ° and ClO3 * were required intermediates in the production of ClO4 − in the O3 experiments. ClOx aqueous oxidation by UV irradiation produced ClO4 − with a large range of δ 18 O values and little or no 17 O anomaly. ClO3 − was produced to a much greater extent than ClO4 − in all experiments except dry oxidation of NaCl by O3 . The isotopic composition of ClO3 − was distinct from that of ClO4 − produced from the same initial reactants. Combined results of O3 and UV mediated reactions largely bracketed the range of natural ClO4 − δ 18 O and Δ 17 O values as well as δ 37 Cl values of non-Atacama natural samples, but no conditions produced the low δ 37 Cl values of Atacama ClO4 − . Our results indicate that variation in production mechanisms, possibly combined with isotopically variable precursors, could be responsible for much of the observed isotopic variation in natural ClO4 − and ClO3 − .